2023
DOI: 10.1002/oby.23691
|View full text |Cite
|
Sign up to set email alerts
|

Association of polycyclic aromatic hydrocarbons with systemic inflammation and metabolic syndrome and its components

Abstract: Objective: This study aimed to evaluate the relationship of polycyclic aromatic hydrocarbon (PAH) exposure with metabolic syndrome (MetS) and its components and to explore the potential mechanism.Methods: Participants from the National Health and Nutrition Examination Survey (NHANES 2001(NHANES -2016 were included.Results: A total of 6532 adults and 1237 adolescents were included in the present analysis. For adults, the odds ratios (ORs) and 95% CIs for each one-unit increase in the log-transformed level of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Overall, we observed associations between 1-hydroxynaphthalene, mono-3-carboxypropyl phthalate and differential placenta methylation, which could lead to alterations in fatty acid metabolism, genetic information processing and organismal systems. Similar results have been presented in the literature, suggesting associations between PAH metabolites and metabolic syndrome, cardiovascular conditions, and systemic inflammation [ 62 , 63 ]. Additionally, a mice-based study suggested prenatal exposure to PAHs and their associated multi-generational (offspring and grand-offspring) epigenetic effects [ 64 ].…”
Section: Discussionsupporting
confidence: 90%
“…Overall, we observed associations between 1-hydroxynaphthalene, mono-3-carboxypropyl phthalate and differential placenta methylation, which could lead to alterations in fatty acid metabolism, genetic information processing and organismal systems. Similar results have been presented in the literature, suggesting associations between PAH metabolites and metabolic syndrome, cardiovascular conditions, and systemic inflammation [ 62 , 63 ]. Additionally, a mice-based study suggested prenatal exposure to PAHs and their associated multi-generational (offspring and grand-offspring) epigenetic effects [ 64 ].…”
Section: Discussionsupporting
confidence: 90%
“…An in vitro study also suggests that cadmium can induce malignant prostate tumors ( 2 , 8 , 29 ). Chronic inflammation caused by beryllium is considered a possible contributor to the carcinogenicity of beryllium to humans ( 24 , 48 ). Currently, there is no research analyzing the synergistic effects of Cd and depression on PSA, and in an era where mental health has a significant impact, further research on the mechanisms and preventive measures is warranted ( 12 , 14 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were observed among drinkers, which may be due to the higher concentration of metals according to our results. Besides, the ORs of total mercury and LTBI in adults and blood manganese with LTBI in adolescents were different in sociodemographic characteristics, which implied more concerns should be given to certain population (29,37,38).…”
Section: Discussionmentioning
confidence: 99%